History of Maleman Tradition in Ramadan and its Changes in Baseng Sub-village Sukoharjo Regency - Ramadzan, Putro Arlianto; Khotimah, Nurul; Nurhaliza, Zilfah (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research aims to examine changes in the Maleman tradition in Baseng sub-village, Sukoharjo Regency, especially regarding changes in implementation, purpose, food, place of serving, and division of food cooking. This research uses a qualitative method with a historical approach, namely by analyzing events in a historical perspective. The data sources used include observation, interviews, and literature studies. Soekmono's cultural theory is seen in the Maleman tradition carried out in Baseng sub-village. The Maleman tradition reflects culture as a human creation that changes according to its needs. The results of this study can be concluded that the Maleman tradition in Baseng sub-village has undergone changes starting from the implementation, the purpose of holding the tradition, food, serving places, and the division of those who cook food. There are changes in the Maleman tradition in Baseng sub-village, the community continues to run it until now. Although not all can and want to participate in carrying out the tradition, they still respect each other.